Pattern recognition receptors in the gut: analysis of their expression along the intestinal tract and the crypt/villus axis. Issue 2 (12th February 2015) - Gourbeyre, Pascal; Berri, Mustapha; Lippi, Yannick; Meurens, François; Vincent‐Naulleau, Silvia; Laffitte, Joëlle; Rogel‐Gaillard, Claire; Pinton, Philippe; Oswald, Isabelle P.
Abstract Pattern recognition receptors (PRRs) play a critical role in the detection of microorganisms and the induction of inflammatory and immune responses. Using PCR and Western‐blot analysis, this study investigated the differential expression in the intestine of 14 PRRs and nine associated cytokines. Thirty‐two pigs were used to determine the expression of these markers (1) along the proximal/distal axis of the small intestine (duodenum, jejunum, and ileum) and (2) between the intestinal segments and their respective lymphoid organs (Peyer's patches [PP] and mesenteric lymph nodes [MLN]). Six additional animals were used to quantify the expression of these genes along the crypt/villus axis of jejunum, using microdissected samples. Most genes showed increased expression (1) in the distal than in the proximal parts of the small intestine (TLR3, 5, RIG‐I, IL‐1β, IL‐8, and IFN‐γ); (2) in lymphoid organs (TLR1, 2, 6, 9, 10, IL‐10, TNF‐α), especially the MLN (TLR4, 7, 8, NOD1, NOD2, NALP3, IFN‐α, IL‐6, IL‐12, and TGF‐β), than in intestinal segments. The analysis along the crypt/villus identified: (1) genes with higher expression in lamina propria (TLR1, 2, 4, 9, NOD1, NOD2, IL‐1β, IL‐10, TGF‐β, TNF‐α) and (2) genes with higher expression in the villus (TLR3, 5, 6, RIG‐I, IL‐6). These results highlight the differential expression of PRRs and cytokines along the proximal/distal and the crypt/villus axis of the intestine, contributing to a fine analysis of the complex functional architecture of the small intestine and should be related to the gut microbiota.